Evaluation of morphological, structural, thermal, electrical, and chemical composition properties of graphene oxide, and reduced graphene oxide obtained by sequential reduction methods - Kaftelen-OdabasI, Hulya (Elsevier, 2024)
This study investigates the preparation and characterization of reduced graphene oxide (RGO) derived from graphene oxide (GO) using various reduction methods, including ethylene glycol (EG), hydrazine, ascorbic acid, thermal reduction, and their sequential combinations. Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA), Raman spectroscopy, and X-ray Photoelectron Spectroscopy (XPS) were employed to analyze the morphological, structural, and thermal properties, as well as the composition and the functional groups of graphene oxide and its reduced forms. The highest electrical conductivity value of about 2500 S/m was obtained after the combined ascorbic acidethylene glycol-hydrazine treatment, which is attributed to the increase in C/O ratio determined by XPS compositional analysis and the decrease in area defects, as confirmed by Raman analysis.
Keywords: Reduced graphene oxide; Chemical reduction; Thermal reduction; multi-step reduction